2005
DOI: 10.1038/emm.2005.30
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc modification on IRS-1 and Akt2 by PUGNAc inhibits their phosphorylation and induces insulin resistance in rat primary adipocytes

Abstract: Abbreviations: GLUT, glucose transporter; HBP, hexosamine biosynthetic pathway; IRS, insulin receptor substrate; PDK-1, phosphatidylinositol dependent protein kinase-1; PKC-λ/ζ, protein kinase C-λ/ζ; PI3K, phospatidylinositol 3-kinase; PM, plasma membrane IntroductionThe pathophysiology of non-insulin-dependent diabetes mellitus (NIDDM) results from impaired peripheral tissue sensitivity to insulin and reduction of insulin secretion. Glucose uptake in mammalian cells is mediated by a family of intrinsic membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 35 publications
5
105
0
3
Order By: Relevance
“…The C. elegans oga-1(ok1207) mutant exhibits increased levels of O-GlcNAc on nuclear pores and other cellular targets and alterations in macronutrient storage and intracellular signaling. In mammals, reduction of O-GlcNAcase activity produces insulin resistance in tissue culture and isolated tissues (39,40,61). These findings, coupled with our previous findings that OGT overexpression produces insulin resistance in mice (17), demonstrate a role for O-GlcNAc cycling in metabolism and insulin signaling.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…The C. elegans oga-1(ok1207) mutant exhibits increased levels of O-GlcNAc on nuclear pores and other cellular targets and alterations in macronutrient storage and intracellular signaling. In mammals, reduction of O-GlcNAcase activity produces insulin resistance in tissue culture and isolated tissues (39,40,61). These findings, coupled with our previous findings that OGT overexpression produces insulin resistance in mice (17), demonstrate a role for O-GlcNAc cycling in metabolism and insulin signaling.…”
supporting
confidence: 65%
“…The oga-1(ok1207) mutation enhanced dauer formation in the sensitized daf-2 mutant background. This resistance to insulin-like signaling in the OGA-1 knockout is highly reminiscent of studies in mammalian cells where enhanced O-GlcNAc levels induced by OGT overexpression (17) or treatment with OGA inhibitors produce insulin resistance (17,39,40,61,80). In contrast, the ogt-1(ok430) mutation displayed hypersensitivity to insulin-like signaling in the dauer assay, suggesting that OGT-1 normally acts to blunt insulin-like signaling (26).…”
Section: Enzymes Of O-glcnac Cycling and Cellular Signaling Cascades mentioning
confidence: 79%
See 1 more Smart Citation
“…5), indicating that additional, intranuclear mechanisms of transactivation exist. It is possible that this mechanism involves GlcNAcylation of upstream regulators of FoxO because AKT and insulin receptor substrate 1 are also GlcNAcylated (47). This mechanism is unlikely, however, because the mutation of a very specific hydroxyamino acid (Thr 317 but not Ser 318 ), which we have shown to be GlcNAcylated, reduces FoxO1 stimulation by hyperglycemia.…”
Section: Discussionmentioning
confidence: 80%
“…Several groups have shown that O-GlcNAc directly inhibits insulin signaling in several cell lines (16 -18). In addition, there are a number of other publications that suggest that the role of O-GlcNAc in Type II diabetes may be cell and protein cell signaling specific to adipocytes (16,25,49), muscles (18), and human coronary artery endothelial cells (17) because others have found that O-GlcNAc did not have any affect on AKT phosphorylation in neuroblastoma cells (50), neural precursor cells (51), and skeletal muscle cells (52). Interestingly, OGT itself, the enzyme responsible for mediating the addition of O-GlcNAc, is known to be involved in insulin signaling (13,24,25), activated by insulin signaling (13), and involved in insulin resistance (24,25).…”
Section: Discussionmentioning
confidence: 99%